2012
DOI: 10.1108/19348831211215678
|View full text |Cite
|
Sign up to set email alerts
|

Bridging rigour and relevance

Abstract: Purpose -The purpose of this paper is to call for an in-depth reflection on Weber's research approach based on the notions of adequate causation and objective possibility. Design/methodology/approach -The paper illustrates the main characteristics and premises of the research approach. It further exemplifies its application through a qualitative study that investigates "How" and "Why" knowledge integration occurs in the creative processes of teams spanning over time and space. In so doing, it argues that Weber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Marshall and Rossman (2016) suggested that by including participant control and data from different sources, the convergence and verification of operational values would provide a more accurate data collection process. Curzi and Rosana (2012) stated that qualitative research focuses on interpreting events and attributing meaning, leaving statistical procedures out of the process, and realizing events in their natural environment. For these reasons, a qualitative case study method appears to be the most appropriate data collection and analysis strategy to seek an answer to the research question in this study.…”
Section: Methodology Selection Of Methodologymentioning
confidence: 99%
“…Marshall and Rossman (2016) suggested that by including participant control and data from different sources, the convergence and verification of operational values would provide a more accurate data collection process. Curzi and Rosana (2012) stated that qualitative research focuses on interpreting events and attributing meaning, leaving statistical procedures out of the process, and realizing events in their natural environment. For these reasons, a qualitative case study method appears to be the most appropriate data collection and analysis strategy to seek an answer to the research question in this study.…”
Section: Methodology Selection Of Methodologymentioning
confidence: 99%